2013
DOI: 10.1080/14631369.2013.784511
|View full text |Cite
|
Sign up to set email alerts
|

Xenophobia online: unmasking Singaporean attitudes towards ‘foreign talent’ migrants

Abstract: In recent years, Singaporeans have become highly anxious about the future of their country and their own personal livelihood due to the influx of educated and professional migrants known as 'foreign talent' and express their ire at the presence of these migrants through xenophobic posts online. This paper suggests that such comments however, are indicative of the feelings of disillusionment and abandonment Singaporeans have towards the People's Action Party -the only government Singaporeans have ever known . W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 2 publications
0
28
0
Order By: Relevance
“…Gomes (2014) suggests that in multicultural Singapore -a country where Singaporeans of Chinese and Indian backgrounds are the dominant ethnicities -there is tension between Singaporean citizens and migrants because citizens view new migrants as different to them, despite the fact that Singaporean citizens may themselves have a similar migrant heritage. Their cultural experiences as Singaporean-born citizens have evolved differently to those who are ethnically similar to them due to historical differences, for example.…”
Section: Australian Multiculturalism and The Missing International Stmentioning
confidence: 96%
“…Gomes (2014) suggests that in multicultural Singapore -a country where Singaporeans of Chinese and Indian backgrounds are the dominant ethnicities -there is tension between Singaporean citizens and migrants because citizens view new migrants as different to them, despite the fact that Singaporean citizens may themselves have a similar migrant heritage. Their cultural experiences as Singaporean-born citizens have evolved differently to those who are ethnically similar to them due to historical differences, for example.…”
Section: Australian Multiculturalism and The Missing International Stmentioning
confidence: 96%
“…The reasons why this ambitious target failed to materialize are manifold, but one important factor has been the rising dissatisfaction expressed by the Singaporean electorate regarding the rapid and voluminous inflows of migrants (temporary or otherwise), especially after the mid-2000s (Gomes 2014;Vasu, Yeap and Chan 2014;Yang 2014a). While authoritative statistics are lacking on the composition of immigrant inflows (due to its perceived sensitiveness), the Chinese certainly comprise one of the largest groups of foreigners in Singapore (Yim 2011).…”
Section: Chinese International Students As 'Foreign Talent' In Singapmentioning
confidence: 99%
“…More recently, the experiences of international students have been supported by the Internet and social media which enable them to use sources of information they are familiar with as well as keep in touch with their friends from home (Chang et al, 2012;Gomes, 2014). Previous studies indicated that international students in Australia use social media to maintain social networks in order to create a space away from home for themselves in addition to the friends they make while in sojourn (Gomes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%